Factors influencing dressing performance after stroke. Issue 8 (August 1991) - Walker, M F; Lincoln, N B
Abstract : Sixty consecutive patients with a diagnosis of stroke were assessed using the Nottingham stroke dressing assessment as well as a series of physical and cognitive assessments. Generally the items of clothing worn on the lower half of the body were significantly correlated with the physical assessments and the items of clothing worn on the upper half were significantly correlated with the cognitive assessments. These results support other studies which suggest that motor recovery and perceptual abilities are important determinants of dressing ability.